PENINGKATAN KEMAMPUAN MENULIS TEKS PERSUASIF DENGAN TEKNIK 3W2H PADA SISWA KELAS VIII A MTs Negeri 2 LAMONGAN TAHUN PELAJARAN 2021/2022 - Zumrotul Ilmiyah (Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to improve the ability to write persuasive texts with the 3W2H technique in class VIII A MTs Negeri Lamongan. The method used in this study is a qualitative method with the type of classroom action research. This research was conducted in two cycles. Each cycle is designed and implemented with the steps of 1) planning, 2) action, 3) observation, and 4) reflection. Sources of data in the study were students of class VIII A MTs Negeri 2 Lamongan while the data in the study were persuasive texts produced by class VIII A students of MTs Negeri 2 Lamongan. Data were analyzed by calculating certain statistics such as mean, the average described using tables. The results showed that the students' ability to write persuasive texts increased with an average of 74% in cycle 1 including in the moderate category, increasing to 91% in cycle 2 including good categories.